IMPACT OF INDUCED EMS MUTAGENESIS ON SEED YIELD OF GROUNDNUT (ARACHIS HYPOGEAE.L) GENOTYPES - A. YUGANDHAR; K. SRINIVAS NAIK; BHATTU RAJESH NAYAK; G. KUMARA JOSHI; G. VIJAY KUMAR (The Journal of Research ANGRAU, 2025)
The aim of the study is to investigate the effect of induced Ethyl methanesulfonat (EMS) on seed yield of three groundnut genotypes under various EMS concentrations. The field work was carried out with three groundnut genotypes viz; ICG2106, ICG5236, ICG76) collected from plant molecular lab, ICRISAT, Hyderabad. The results showed that all three genotypes recorded lower seed yield under 0.3 percent EMS, 0.4 percent EMS, and 0.5 percent EMS over their control where as in M2 generation the results showed that all three genotypes recorded higher seed yield under 0.3% EMS, 0.4% EMS, and 0.5% EMS over their control. ICG2106 was recorded higher seed yield at 0.3% EMS (37.90 gm per plant), 0.4% MS (33.90 gm per plant) and 0.5% EMS (32.30 gm per plant) over its control plant (24.70) and compare to their other genotypes. It was observed the higher seed yield was at 0.3% EMS followed by 0.4% EMS and 0.5% EMS. It is revealed that when the concentration of EMS increased the seed yield of the groundnut is increased in M2 generation.It is revealed that when the concentration of EMS increased the seed yield of the groundnut is decreased in M1 generation and increased in M2 generation. Hence highest increase of seed yield was observed by the variety ICG2106- 0.3% (37.90 gm) followed by ICG5236- 0.3% (30.30 gm) and ICG76- 0.3% (29.97gm) under three various EMS concentrations in M2 generation.